EFFECTS OF TWO TYPES OF TRUNK EXERCISES ON BALANCE AND ATHLETIC PERFORMANCE IN YOUTH SOCCER PLAYERS - Imai, Atsushi (Sports Physical Therapy Section, 2014)
PURPOSE/BACKGROUND: Many athletes perform trunk stabilization exercises (SE) and conventional trunk exercises (CE) to enhance trunk stability and strength. However, evidence regarding the specific training effects of SE and CE is lacking and there have been no studies for youth athletes. Therefore, the purpose of this study was to investigate the training effects of SE and CE on balance and athletic performance in youth soccer players. METHODS: Twenty‐seven male youth soccer players were assigned randomly to either an SE group (n = 13) or CE group (n = 14). Data from nineteen players who completed all training sessions were used for statistical analyses (SE, n = 10; CE, n = 9). Before and after the 12‐week intervention program, pre‐ and post‐testing comprised of a static balance test, Star Excursion Balance Test (SEBT), Cooper’s test, sprint, the Step 50, vertical jump, and rebound jump were performed. After pre‐testing, players performed the SE or CE program three times per week for 12 weeks. A two‐way repeated‐measures ANOVA was used to assess the changes over time, and differences between the groups. Within‐group changes from pre‐testing to post‐testing were determined using paired t‐tests. Statistical significance was inferred from p < 0.05. RESULTS: There were significant group‐by‐time interactions for posterolateral (p = 0.022) and posteromedial (p < 0.001) directions of the SEBT. Paired t‐tests revealed significant improvements of the posterolateral and posteromedial directions in the SE group. Although other measurements did not find group‐by‐time interactions, within‐group changes were detected indicating significant improvements in the static balance test, Cooper’s test, and rebound jump in the only SE group (p < 0.05). Vertical jump and sprint were improved significantly in both groups (p < 0.05), but the Step 50 was not improved in either group (p > 0.05). CONCLUSIONS: Results suggested that the SE has specific training effects that enhance static and dynamic balance, Cooper’s test, and rebound jump. LEVEL OF EVIDENCE: 3b